Masadir al-Istidlal wa Manhajihi 'Inda al-Imam al-Fandalawi fi Kitabihi (Tahzib al-Masalik fi Nasrah Mazhab Malik) - Sadeg Mohamed, Sadeg Mabrok; Ali, Abdul Karim (Jurnal Fiqh, 2010)
Imam al-Fandalawi is one of the Imam from Maliki School in VI Hijri. He has several books including Tahdhib al-Masalik fi Nusrat Madhhab Malik. Therefore, this article attempts to elucidate the background of Imam al-Fandalawi as well as his academic status and sources of his inferences. This article also focuses on his methodology of istidlal based on his book, in order to support the Maliki School.